Correlation between Diabetes Melitus Type II and knee Oosteoarthritis in Wahiddin Sudirohusodo Hospital - Merryawan, Cristmos Bambang; Rasjad, Chairuddin; Prihantono, Prihantono; Arifin, Seweng (Saintika Medika: Jurnal Ilmu Kesehatan dan Kedokteran Keluarga, 2020)
This research is aimed to find out the correlation between Diabetes Mellitus Type II and the incidence of knee osteoarthritis in Wahiddin Sudirohusodo Makassar Â Hospital.This research was a case-control conducted on outpatients in the Orthopedic Division of the Department of Surgery, Wahiddin Sudirohusodo General Hospital. There were 51 cases and 51 controls were randomly selected using secondary data from medical records in the period of May 2017 to May 2018.The results indicate that the patients have an average age of 55.15 + 8.78 years with the majority female gender of 72 people (70,6%). The patient had a mean blood sugar level of 195,84 + 83,4. Bivariate analysis between knee OA and DM type II obtained the value of Odd Ratio i.e. OR = 4.320 (95% Confidence Interval 1.791-10.425). There is a significant correlation between knee osteoarthritis and type II DM with the incidence of knee osteoarthritis (p = 0.002). Type II Diabetes Mellitus increases the risk 4 times to knee osteoarthritis OR = 4.320 (95% Confidence Interval 1.791-10.425).